2009
DOI: 10.1021/jp806565a
|View full text |Cite
|
Sign up to set email alerts
|

Water Structure at the Air−Aqueous Interface of Divalent Cation and Nitrate Solutions

Abstract: The water surface structure of aqueous magnesium, calcium, and strontium nitrate solutions with six to seven water molecules on average solvating each ion was investigated using vibrational sum frequency generation (VSFG) spectroscopy. Raman (polarized) and infrared spectroscopies were used for understanding solvation effects. Infrared reflection spectra were analyzed to further understand the VSFG data. The VSFG spectral changes indicate that the divalent countercation species play a key role in the surface p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 37 publications
4
63
0
Order By: Relevance
“…The influence of molecular anions such as NO 3 − , SO 4 2− , and CO 3 2− on the hydrogen-bonding structure of water has also been the focus of many VSFG studies (14,44,48,49,53,57,96). An understanding of the VSFG results for polyatomic anion-containing solutions in the water hydrogen-bonding region proves more elusive than that for the halide salt solutions.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The influence of molecular anions such as NO 3 − , SO 4 2− , and CO 3 2− on the hydrogen-bonding structure of water has also been the focus of many VSFG studies (14,44,48,49,53,57,96). An understanding of the VSFG results for polyatomic anion-containing solutions in the water hydrogen-bonding region proves more elusive than that for the halide salt solutions.…”
Section: Figurementioning
confidence: 99%
“…Beyond examining the water structure at the vapor/neat water interface, there is much interest in elucidating molecular behavior via VSFG at the vapor/water interface for a wide variety of chemical systems. With perspective toward understanding the role that tropospheric aqueous aerosols play in atmospheric chemistry, among other applications, VSFG has been applied to study the behavior that inorganic ions (25,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57), small molecular solutes (25,(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69), and lipids (32, 35,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]…”
Section: Introductionmentioning
confidence: 99%
“…18 There have been no other VSFG studies on nitrate salts other than NaNO 3 except that from Allen and co-workers of aqueous Mg(NO 3 ) 2 , Ca(NO 3 ) 2 , and Sr(NO 3 ) 2 . 27 These nitrate-mode and hydrogenbonding studies suggested that NO 3 − ions, and their corresponding ion pairs, approach the aqueous surface and that interfacial ion pairing between NO 3 − and divalent cations (Mg 2+ , Ca 2+ , Sr 2+ ) followed the trend of increasing inversely with the cation charge density. 55 In the work presented here, selected nitrate salt solutions (LiNO 3 , NaNO 3 , NH 4 NO 3 , and Mg(NO 3 ) 2 ) and their interfacial ion distributions are investigated using VSFG and HD-VSFG spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 98%
“…The specific study of aqueous nitrate at the vapor interface has received much attention because it is abundant in the atmosphere and involved in a variety of reactions therein. [1,2] Second harmonic generations (SHG) and vibrational sum frequency generation (VSFG) have been instrumental in developing an understanding of the relationship between ion concentration (between 1 M and 6.8 M) [3][4][5][6][7][8][9] and the meso-scale interfacial properties in the liquid:vapor system (e.g. surface tension, interfacial width) as well as the orientation of interfacial nitrate relative to the bulk liquid.…”
Section: Introductionmentioning
confidence: 99%